Telaah Atas Tasawuf Buya HAMKA Tentang Kesehatan Jiwa - Khudori Husnan (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2014)
Nurcholish Madjid has pointed out that HAMKA (Haji Abdul Malik Karim Amrullah) was the pioneer of Neosufism in the country. This scholar developed a deep religious spirituality without seeking isolation from society. He suggested that a Sufi (Muslim mystic) should be active in society. HAMKA concept not separate from knowing God as another manifestation of the love of God which is the highest love that exists in the universe, including the love that also exists between the opposite sex. According to HAMKA, this love must be sacred and to be based on devotion to God. HAMKA raises love as a common theme that characterizes Western romance in addition to other characteristics. Through the power of imagination and creativity, know- ledge, experience and insight of Islam of HAMKA, then the romanticism becomes more Islamic (Sufism) as an indicator of his predicate as a philo- sopher, artist and scholar.